A whack on the side of the head how to unlock your mind for innovation - Von Oech, Roger (Warner Books, Inc., 1983)
This is a book about the ten mental locks that prevent you from being more innovative and what you can do to open them. Many of the ideas presented here come from the author's experiences as a creative thinking consultant in industry. During the past five years he had the opportunity to work with many innovative and/or interesting companies. He worked with people in marketing, engineering, data processing, finance, research and development, television, and retail. This book contains stories, anecdotes, insights, and ideas that came out of the workshops he conducted as well as many of his own thoughts about what can make you more creative.